Predictors of Intention to Get a COVID-19 Vaccine of Health Science Students: A Cross-Sectional Study - Nguyen VT; Nguyen MQ; Le NT; Nguyen TNH; Huynh G (Dove Medical Press, 2021)
Van Tap Nguyen,1 Minh Quan Nguyen,2 Ngoc Thi Le,3 Thi Ngoc Han Nguyen,4 Giao Huynh5 1Faculty of Medicine, Tra Vinh University, Tra Vinh City, Tra Vinh Province, Vietnam; 2Department of Scientific Research, Thu Duc District Hospital, Ho Chi Minh City, Vietnam; 3Health Management Training Institute, Hanoi University of Public Health, Hanoi City, Vietnam; 4Infection Control Department, University Medical Center at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 5Faculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, VietnamCorrespondence: Minh Quan NguyenDepartment of Scientific Research, Thu Duc District Hospital, 29 Phu Chau St, Thu Duc City, Ho Chi Minh City, VietnamTel +84 799835555Email minhquanbvtd@gmail.comBackground: Vaccination is one of the interventions that can be employed to control coronavirus disease (COVID-19). The aim of this study is to identify factors that affect vaccination intention among health science students, by using the health belief model (HBM) as a theoretical framework.Methods: This study was undertaken in April 2021 using a convenience sample strategy among health science students in Tra Vinh University, which is a university in South Vietnam. Participants were required to complete the self-report questionnaire. All data were calculated by using STATA 14 software, to determine the factors associated with COVID-19 vaccine acceptance, a multivariable logistic regression analysis was performed, along with odds ratio (OR) and 95% confidence interval (95% CI).Results: A total of 412 eligible participants were taken part in the study, with a questionnaire response rate of 48.2%, reporting that 77.7% of participants intended to receive a COVID-19 vaccination when available. An overall score of knowledge was 7.8 ± 1.5 (range 0- 10), a positive attitude toward vaccination including perceived susceptibility and severity (3.1 ± 0.7), perceived benefits (3.1 ± 0.7) and cues to action (4.0 ± 0.6). Determinants of willingness to get a COVID-19 vaccination included their field of education, knowledge and factors in HBM model including perceived susceptibility and severity, perceived benefits and cues to action (all p < 0.05). In contrast, perceived barriers had a negative association with the probability of vaccine acceptance (p < 0.05). The study did indicate a number of participants not willing to receive a vaccination due to, mainly, safety (67.4%), development issues (58.7%) and side effects (79.3%).Conclusion: The theoretical framework recognized factors that influence vaccine acceptance. These are considered evidence for the development of planning strategies to optimize the vaccination uptake and offer success in vaccination campaigns for both health science students and the general population.Keywords: COVID-19 vaccine, health science, student, intention, Vietnam